Assessment of phenolic compounds stability and retention during spray drying of phyllanthus niruri extracts - Gimbun, J.; Nguang, S.L.; Pang, S.F.; Yeong, Y.L.; Kee, K.L.; Chin, S.C. (American Chemical Society (ACS Publications), 2019)
This paper presents a method to enhance the thermal stability of Phyllanthus niruri polyphenols during spray drying. The major polyphenol content of the extracts derived from the aerial part of the plant was analyzed, using ultra-high-performance liquid chromatography, whereas the surface composition of the microcapsule was analyzed by X-ray photoelectron microscopy (XPS). Three encapsulant formulations that were made of maltodextrin (MD), whey protein isolate (WPI), and their combinations (WPI:MD = 1:9) were compared with a control formulation without encapsulation. The microencapsulation method by WPI:MD proposed in this work increased the average polyphenols retention percentage after spray drying from 72.7% (without encapsulation) to 87.2%. The powder encapsulated with WPI:MD (1:9) yielded the best retention of phyllanthin (84.33%), gallic acid (88.93%), and quercetin (88.39%), compared to the system encapsulated solely by WPI or MD. The XPS results confirmed the existence of surface protein, which acts as a protective layer, thereby enhancing the polyphenols stability in the microcapsule. The finding from this work shows that quercetin is more susceptible to thermal degradation than phyllanthin and gallic acid during spray drying.